Clinical Approach to Jaundice Patients - Lidia Dewi; Boy Hutaperi (PT. Anagata Sembagi Education, 2025)
This article aims to provide a comprehensive clinical approach to the evaluation and management of patients with jaundice, emphasizing differential diagnosis, diagnostic algorithms, and therapeutic implications through a case-based discussion. This descriptive-analytical study utilizes a case-based approach for an adult patient with jaundice. Data were obtained from clinical examination, laboratory assessment of liver function, and abdominal imaging for structural evaluation. Jaundice, characterized by yellow discoloration of the skin and sclera due to hyperbilirubinemia, can be divided into pre-hepatic, intra-hepatic, and post-hepatic jaundice. A systematic clinical approach through history taking, physical examination, and evaluation of biochemical parameters such as AST, ALT, ALP, GGT, and bilirubin fractions is crucial in determining the etiology. The case presented suggests intrahepatic cholestasis due to hepatitis, which was confirmed by laboratory and imaging studies. Early identification of the cause of jaundice is crucial for determining management and prognosis. This article emphasizes the importance of using clinical algorithms to differentiate between hepatic and obstructive causes to avoid unnecessary procedures and improve patient clinical outcomes.